Analisis Semiotika Kritik Sosial Politik Lagu (Studi Kasus Lagu “Punya Apa Lagi” Karya Iksan Skuter) - Ghoffur, Ahmad Abdul; Ni’am, Harun (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2025)
Independent music or indie music has an idealism in playing songs without having to look at the market and music industry while still providing the best music and innovation. In it there is often socio-political criticism. The song